Pembelajaran Dengan Quantitative Reasoning Pemecahan Masalah Pada Mata Kuliah Teori Bilangan - Fetty Nuritasari; Devie Reztia Anjarani (IndoMath: Indonesia Mathematics Education, 2019)
The objectives of the study: 1. examine questions related to Quantitative Reasoning; 2. It is expected that questions related to Quantitative Reasoning can be given and trained to students. The indicators show a student have problem solving skills are: 1. Understanding the problem; 2. Determine the right settlement strategy; 3. Implement the chosen strategy; 4. Determine the solution to the problem; 5. Checking the accuracy of the strategy and the correctness of the solutions. The results showed that students with upper, middle and lower ability at the stage of problem solving were described by gathering information obtained from the questions. In the upper subject, it works quite well. This is due to the functioning of the Quantitative Reasoning component in solving problems.. Whereas in the lower subject, it also occurs incomplete. This is due to the malfunctioning component of information reception.